Clostridium acetobutylicum grows vegetatively in a biofilm rich in heteropolysaccharides and cytoplasmic proteins - Dong Liu; Zhengjiao Yang; Yong Chen; Wei Zhuang; Huanqing Niu; Jinglan Wu; Hanjie Ying (Biotechnology for Biofuels, 2018)
Abstract Background Biofilms are cell communities wherein cells are embedded in a self-produced extracellular polymeric substances (EPS). The biofilm of Clostridium acetobutylicum confers the cells superior phenotypes and has been extensively exploited to produce a variety of liquid biofuels and bulk chemicals. However, little has been known about the physiology of C. acetobutylicum in biofilm as well as the composition and biosynthesis of the EPS. Thus, this study is focused on revealing the cell physiology and EPS composition of C. acetobutylicum biofilm. Results Here, we revealed a novel lifestyle of C. acetobutylicum in biofilm: elimination of sporulation and vegetative growth. Extracellular polymeric substances and wire-like structures were also observed in the biofilm. Furthermore, for the first time, the biofilm polysaccharides and proteins were isolated and characterized. The biofilm contained three heteropolysaccharides. The major fraction consisted of predominantly glucose, mannose and aminoglucose. Also, a great variety of proteins including many non-classically secreted proteins moonlighting as adhesins were found considerably present in the biofilm, with GroEL, a S-layer protein and rubrerythrin being the most abundant ones. Conclusions This study evidenced that vegetative C. acetobutylicum cells rather than commonly assumed spore-forming cells were essentially the solvent-forming cells. The abundant non-classically secreted moonlighting proteins might be important for the biofilm formation. This study provides the first physiological and molecular insights into C. acetobutylicum biofilm which should be valuable for understanding and development of the biofilm-based processes.